CRITICAL THINKING AND THE USE OF ARTIFICIAL INTELLIGENCE (AI) - Caldelas, Francisco Roberto Rojas; Álvarez, Marco Antonio Marín (Seven Editora, 2026)
In the first quarter of the 21st century, technological advances — digitalization and artificial intelligence — have profoundly transformed social, educational, and cultural dynamics; however, this progress has coincided with a phenomenon of weakening critical thinking, characterized by the primacy of immediacy, subjectivity, and information overload; this article analyzes the historical evolution of critical thinking from its origins in classical philosophy to its role in modernity, highlighting its function as a fundamental tool for rational decision-making, ethics, and democratic life; it also examines the impact of digital culture, the Google effect, and cognitive externalization on the decline of reflective capacities; from the field of graphic design education, it is argued that the uncritical incorporation of digital technologies and artificial intelligence has displaced humanistic and methodological approaches, privileging immediate production and formal perfection over analysis, meaning, and the social context of images; finally, the study proposes the need to reconfigure educational models in graphic design through a theoretical, critical, and reflective perspective that enables the integration of artificial intelligence without abandoning the development of critical thinking and the construction of meaning in contemporary visual culture.